Supplemental food for Amblyseius swirskii in the control of thrips: feeding friend or foe?. Issue 3 (13th April 2015) - Vangansbeke, Dominiek; Nguyen, Duc Tung; Audenaert, Joachim; Verhoeven, Ruth; Gobin, Bruno; Tirry, Luc; De Clercq, Patrick
Abstract: BACKGROUND: In integrated pest management systems in greenhouse crops, the predatory mite Amblyseius swirskii is becoming increasingly important as a biological control agent of various pests, especially thrips and whiteflies. An emerging strategy to promote the predator's establishment and retention in the crop consists in providing food supplements. However, when faced with omnivorous pests, such as the western flower thrips, Frankliniella occidentalis, food supplements need to be applied with extreme care, in order not to boost population growth of the pest. This laboratory study was conducted to evaluate the impact of commercial products of Typha angustifolia pollen and decapsulated brine shrimp cysts ( Artemia sp.) on populations of both pest and predator and on predator–prey interactions. RESULTS: Pollen was highly supportive for both F. occidentalis and A. swirskii, whereas Artemia cysts supported thrips populations to a lesser extent than those of the predator. Furthermore, a less pronounced reduction in thrips consumption by A. swirskii was observed in the presence of Artemia cysts as compared with T. angustifolia pollen. CONCLUSION: Artemia might be a valuable alternative to pollen for supporting populations of A. swirskii in order to improve thrips management, as they are less beneficial for the pest but do support population growth of A. swirskii . © 2015 Society of Chemical Industry